Shared parenting and parents' income evolution after separation: New explorative insights from Germany - Christina Boll; Simone Schüller (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Based on panel data from 1997 to 2018, we investigate the socioeconomic preconditions and economic consequences of 'shared parenting (SP)' forms in Germany. Referring to the post-separation year, we build SP groups from information on child residence and fathers' childcare hours during a regular weekday. We explore the short-term gender and SP group associations with economic well-being as well as, for mothers only, its medium-term associations in the five years after separation. Our findings indicate that around separation, intense SP is a superior strategy in terms of equivalized household income. This also holds true for mothers in the medium-term, but their earnings barely improve during that time. Mothers stay highly involved in childcare even in shared parenting settings and/or fail to redirect released childcare time to the labor market. Our data support the notion that even high resources do not shield mothers against remaining trapped in economic dependence post-separation.
Keywords: J12; J13; J22; 330; union dissolution; shared parenting; childcare; child residence; household income; earnings; household composition; SOEP